Optimization of pillar electrodes in subretinal prosthesis for enhanced proximity to target neurons. (5th March 2018) - Flores, Thomas; Lei, Xin; Huang, Tiffany; Lorach, Henri; Dalal, Roopa; Galambos, Ludwig; Kamins, Theodore; Mathieson, Keith; Palanker, Daniel
Abstract: Objective . High-resolution prosthetic vision requires dense stimulating arrays with small electrodes. However, such miniaturization reduces electrode capacitance and penetration of electric field into tissue. We evaluate potential solutions to these problems with subretinal implants based on utilization of pillar electrodes. Approach . To study integration of three-dimensional (3D) implants with retinal tissue, we fabricated arrays with varying pillar diameter, pitch, and height, and implanted beneath the degenerate retina in rats (Royal College of Surgeons, RCS). Tissue integration was evaluated six weeks post-op using histology and whole-mount confocal fluorescence imaging. The electric field generated by various electrode configurations was calculated in COMSOL, and stimulation thresholds assessed using a model of network-mediated retinal response. Main results . Retinal tissue migrated into the space between pillars with no visible gliosis in 90% of implanted arrays. Pillars with 10 μ m height reached the middle of the inner nuclear layer (INL), while 22 μ m pillars reached the upper portion of the INL. Electroplated pillars with dome-shaped caps increase the active electrode surface area. Selective deposition of sputtered iridium oxide onto the cap ensures localization of the current injection to the pillar top, obviating the need to insulate the pillar sidewall. According to computational model, pillars having a cathodic return electrode above the INL and active anodic ring electrode at the surface of the implant would enable six times lower stimulation threshold, compared to planar arrays with circumferential return, but suffer from greater cross-talk between the neighboring pixels. Significance . 3D electrodes in subretinal prostheses help reduce electrode-tissue separation and decrease stimulation thresholds to enable smaller pixels, and thereby improve visual acuity of prosthetic vision.